Second Harmonic Generation Based on Strong Field Enhancement in Metallic Nanostructured Surface - Kitsakorn LOCHAROENRAT (My University, 2014)
Although absorption is still the primary optical property of interest, other spectroscopic techniques including optical second harmonic generation (SHG) are also used to understand anisotropic nature of nanomaterials. Benefit of SHG technique as compared with linear optical approach is that SH response is the most sensitive to surface potential changes and SH intensity mainly comes from surface/interface layers. This article reports that optical absorption spectra due to surface plasmon modes of metallic nanowires exhibit strong anisotropic absorption. Maxwell-Garnett simulation cannot fit with experimental results because of wire sizes much larger than wavelength of light, whereas finite-difference time-domain calculation can fit well with experimental findings in terms of position of photon energy of absorption peak with respect to polarization conditions. DOI: http://dx.doi.org/10.5755/j01.ms.20.4.6399
Keywords: Nanomaterials; Two-Photon Absorption; Plasmonic and Surface Plasmon Research